2013
DOI: 10.1371/journal.pone.0066469
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Novelty Relies on Dopaminergic Signaling: Evidence from Apomorphine's Impact on the Novelty N2

Abstract: Despite much research, it remains unclear if dopamine is directly involved in novelty detection or plays a role in orchestrating the subsequent cognitive response. This ambiguity stems in part from a reliance on experimental designs where novelty is manipulated and dopaminergic activity is subsequently observed. Here we adopt the alternative approach: we manipulate dopamine activity using apomorphine (D1/D2 agonist) and measure the change in neurological indices of novelty processing. In separate drug and plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…This link may in part be mediated by DA release in the cortex, where noradrenergic terminals co-release DA [39]. Indeed, a few studies have reported evidence that DA agents affect the centroparietal P3 to unexpected and novel stimuli, although primarily when these were task-irrelevant [38,85,86]. This link between catecholamine release and the P3 is not exclusive, because the centroparietal P3 is also modulated by pharmacological manipulations of the cholinergic system [87,88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This link may in part be mediated by DA release in the cortex, where noradrenergic terminals co-release DA [39]. Indeed, a few studies have reported evidence that DA agents affect the centroparietal P3 to unexpected and novel stimuli, although primarily when these were task-irrelevant [38,85,86]. This link between catecholamine release and the P3 is not exclusive, because the centroparietal P3 is also modulated by pharmacological manipulations of the cholinergic system [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…First, we used the centroparietal P3 component of the EEG as an electrophysiological correlate of outcome-evoked phasic catecholamine release in the cortex [3538] (but see the Discussion for a competing hypothesis), and examined trial-by-trial relationships between prediction-error magnitude, P3 amplitude and learning rate using multilevel mediation analyses. Second, we examined the relationships between P3 amplitude and two latent variables—capturing the unexpectedness of an outcome and the uncertainty about the outcome-generating process—that together determine learning rate according to a previously established normative model [4,5,21].…”
Section: Introductionmentioning
confidence: 99%
“…The neural basis of the reward-related enhancement of cognitive control may rely on dopaminergic pathways that are known to be involved in both reward processing [3538] and conflict processing [39, 40]. Interestingly, processing of novel information was also shown to activate dopaminergic pathways [41, 42]. Therefore, manipulating stimulus’ novelty may support response selection and inhibition through the dopaminergic pathways [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a recent study found a correlation between brain activity in the midbrain and ventral striatum, and value attributed to novelty while engaging in a decision-making task, as well as between the same brain areas and novelty-seeking traits (Wittmann et al, 2008). Moreover, pharmacological manipulation studies observed a correlation between increase in dopamine levels and novelty detection in humans (Rangel-Gomez et al, 2013) as well as novelty-seeking in animals (Costa et al, 2014). Furthermore, genetic studies have emphasised the importance of D2 receptors in the regulation of exploration versus exploitation behaviour (Frank & Hutchison, 2009).…”
Section: Introductionmentioning
confidence: 99%